Social Networks in Regulation Learning Process Quality - Gulbis, Rūdolfs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Successful web-based learning depends on several key factors. These include the quality of the learning tools, the motivation of users, and the credibility of the learning materials as well as their significance in the eyes of users. It is possible to find numerous examples of web-based lifelong learning approaches that can be viewed on social networks and discussion forums. The research for this study included designing several blog-based discussion forums where user activities were logged and the results were compared to usercompleted questionnaires for similar activities. Several user behaviour identification models were designed based on algorithmically computed tallies of user behaviours. These models are currently being applied for further study to measure user behaviours in virtual learning environments.